Awareness of venous thromboembolism in mental health services for older people. Issue 4 (2nd September 2013) - van, M.; Wieczorek, G.; Reilly, J.
<x xml:space="preserve">Abstract</x> Accessible summary Venous thromboembolism (VTE) is an important safety issue in the inpatient mental health care of older people. In a survey of specialist mental health staff, knowledge of deep vein thrombosis was good. More variable awareness of the presentation and risk factors for pulmonary embolism indicates the need for training integrated into regular physical health care updates. Abstract Currently, failure to adequately screen and prevent venous thromboembolism (VTE) is estimated to cause between 25 000 and 32 000 potentially avoidable deaths annually in the United Kingdom. The authors aimed to assess the awareness of VTE in clinical staff working in Mental Health Services for Older People, Tees, Esk and Wear Valleys National Health Service Foundation Trust. A questionnaire was devised to assess knowledge of VTE symptoms, risk factors, prevention, and treatment in clinical staff working in Mental Health Service for Older Peoples' inpatient units. Forty‐nine nurses, 12 consultant psychiatrists, and 11 clinical pharmacists responded. A significant proportion of staff had previous involvement in VTE treatment. Staff had significantly more limited knowledge of pulmonary embolism compared to deep vein thrombosis with areas for improvement in presentation, risk factors, and prevention. The study confirms a need for improved awareness among all clinical staff including nurses, pharmacists, and doctors, which can be met by including VTE awareness in First Response training, and encouraging use of the Department of Health VTE e‐learning tool.